2022
DOI: 10.1140/epjc/s10052-022-10005-9
|View full text |Cite
|
Sign up to set email alerts
|

On the ambiguity between differential and integral forms of the Martin–Ryskin–Watt unintegrated parton distribution function model

Abstract: In this work, we study the structure of the leading order Martin–Ryskin–Watt (MRW) unintegrated parton distribution function (UPDF) and explain in detail why there exists discrepancy between the two different definitions of this UPDF model, i.e., the integral (I-MRW) and differential (D-MRW) MRW UPDFs. We perform this investigation with both angular and strong ordering cutoffs. The derivation footsteps of obtaining the I-MRW UPDF from the D-MRW ones are numerically performed, and the reason of such non-equival… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…While we found Ref [15]. interesting, we do not fully agree with the claim that the only difference between the KMR[10,22] and WMR[11] approaches is the use of the cutoffs.…”
contrasting
confidence: 82%
See 4 more Smart Citations
“…While we found Ref [15]. interesting, we do not fully agree with the claim that the only difference between the KMR[10,22] and WMR[11] approaches is the use of the cutoffs.…”
contrasting
confidence: 82%
“…More recently, the authors of Ref. [15] showed that a good numerical agreement between the differential and integral definitions is obtained if one combines the conditions of Refs. [12] and [13], i.e., cutoffs-dependent PDFs, and Eq.…”
Section: Cutoff-dependent Pdfsmentioning
confidence: 96%
See 3 more Smart Citations